2004
DOI: 10.1016/s1074-7613(04)00234-1
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization of TNF Receptor 1 SignalingInternalized TNF Receptosomes as Death Signaling Vesicles

Abstract: The molecular regulation of the recruitment of initial signaling complexes at the TNF-R1 is poorly defined. We demonstrate here that within minutes internalized TNF-R1 (TNF receptosomes) recruits TRADD, FADD, and caspase-8 to establish the "death-inducing signaling complex" (DISC). In addition, we identified the TNF-R1 internalization domain (TRID) required for receptor endocytosis and provide evidence that TNF-R1 internalization, DISC formation, and apoptosis are inseparable events. Analyzing cell lines expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
311
0
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(341 citation statements)
references
References 2 publications
15
311
0
11
Order By: Relevance
“…In the first, which occurs at the cell membrane in association with the activated TNFR1 receptor, TRADD interacts with TNFR1, TRAF proteins, and RIP, and this leads primarily to antiapoptotic signaling. After TNFR1 stimulation, a cytoplasmic complex 16 or a complex in endocytic vesicles 17 involving TRADD interactions with FADD leads to caspase-8-dependent apoptosis. Finally a third, nuclear complex that does not involve FADD or caspase-8 can also lead to apoptosis, but this occurs through caspase-9 and leads to both caspase-dependent and caspase-independent effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first, which occurs at the cell membrane in association with the activated TNFR1 receptor, TRADD interacts with TNFR1, TRAF proteins, and RIP, and this leads primarily to antiapoptotic signaling. After TNFR1 stimulation, a cytoplasmic complex 16 or a complex in endocytic vesicles 17 involving TRADD interactions with FADD leads to caspase-8-dependent apoptosis. Finally a third, nuclear complex that does not involve FADD or caspase-8 can also lead to apoptosis, but this occurs through caspase-9 and leads to both caspase-dependent and caspase-independent effects.…”
Section: Discussionmentioning
confidence: 99%
“…17 However, we previously showed that N-Benzyloxcarbonyl-Val-Ala-Asp(o-Me) fluoromethyl ketone (zVAD.fmk), which inhibits caspase-8-dependent apoptosis, was unable to block cell death induced by a nuclear TRADD molecule, 18 suggesting that nuclear TRADD works independently of these proteins. To test this hypothesis, we expressed a truncated TRADD death domain molecule that retains the nuclear import sequence but has no nuclear export sequence and is exclusively nuclear 18 (nuclear TRADD) or a TRADD mutant that is exclusively in the cytoplasm (cytoplasmic TRADD) through the addition of a myristolation signal that anchors it to the cell membrane preventing nuclear shuttling ( Figure 1a).…”
Section: Nuclear Tradd-induced Death Is Caspase-8 and Fadd-independentmentioning
confidence: 99%
See 1 more Smart Citation
“…Clathrin-mediated endocytosis of TNFR1 and Fas has been shown to be required for apoptosis stimulation, but not for activation of the NF-kB and MAPK pathways. It has been reported that in response to TNF or FasL, DISC components are directly recruited to internalized receptors residing in endosomal compartments, dubbed receptosomes (Schneider-Brachert et al, 2004Lee et al, 2006). By contrast, recruitment of the signaling complexes that drive NF-kB and MAPK activation in response to TNFR1 or Fas ligation occurs at the cell surface and does not rely on receptor internalization (Schneider-Brachert et al, 2004Lee et al, 2006).…”
Section: Recent Advances In Understanding Apoptosis Initiationmentioning
confidence: 99%
“…It has been reported that in response to TNF or FasL, DISC components are directly recruited to internalized receptors residing in endosomal compartments, dubbed receptosomes (Schneider-Brachert et al, 2004Lee et al, 2006). By contrast, recruitment of the signaling complexes that drive NF-kB and MAPK activation in response to TNFR1 or Fas ligation occurs at the cell surface and does not rely on receptor internalization (Schneider-Brachert et al, 2004Lee et al, 2006). Recent work suggests that actin polymerization and internalization events are required for Fas activation by agonistic antibody but not FasL (Chaigne-Delalande et al, 2009).…”
Section: Recent Advances In Understanding Apoptosis Initiationmentioning
confidence: 99%